The Effect of Shadow Fighting Training on Blocking Speed in Pencak Silat Athletes - Hasanuddin, M. Irfan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Pencak Silat is a traditional Indonesian martial art that requires exceptional defensive skills, particularly in blocking techniques. Shadow fighting training has emerged as a potential method to enhance blocking speed and reaction time in athletes. This study aims to investigate the effect of shadow fighting training on blocking speed performance in Pencak Silat athletes. We conducted a quasi-experimental study with 30 Pencak Silat athletes, aged 18-25 years, dividing them into experimental (n=15) and control groups (n=15). The experimental group underwent 8 weeks of shadow fighting training (3 sessions per week, 60 minutes per session), while the control group continued regular training. Blocking speed was measured using reaction time tests and blocking movement analysis before and after the intervention. The experimental group showed significant improvement in blocking speed (p<0.05), with mean reaction time decreasing from 0.47±0.08 seconds to 0.32±0.06 seconds. The control group showed no significant changes (p>0.05). Post-intervention comparison between groups revealed significantly faster blocking speed in the experimental group (p<0.01). Conclusion: Shadow fighting training effectively improves blocking speed in Pencak Silat athletes and can be recommended as a supplementary training method for enhancing defensive performance.